Nanopartículas de copolímero em bloco de maltoheptaose-b-polimetilmetacrilato contendo ftalocianina de cloro-alumínio para o uso em terapia fotodinâmica - Stefanello, Luiza Bertoldo (2022)
New nanocarriers have been contributing to the development of so-called third-generation photosensitizers for use in photodynamic therapy (PDT). Chloro-aluminum phthalocyanine (ClAlPc) is a promising second-generation photosensitizer for use in PDT, that exhibits adequate singlet oxygen quantum yield (ΦΔ), strong absorption at the phototherapeutic window (600 - 800 nm) and low photodegradation. However, ClAlPc is characterized by highly hydrophobic, it’s resulting in a poor solubility in the physiological medium. To overcome this fact, the encapsulation of ClAlPc in nanocarriers is essential to promote a better bioavailability of the drug in the organism and consequently improve the phototherapeutic activity. Thus, the objective of this work was to encapsulate ClAlPc in MH-b-PMMA block copolymer nanocarriers (MH-b-PMMA@ClAlPc) and evaluate its photodynamic activity. As a comparison, this work also had the objective to encapsulate ClAlPc in poly-ε-caprolactone nanocapsules and in nanoemulsions of commercial surfactants (Span 60® and Tween 80® ). The physicochemical characterization of the nanoparticles was performed through hydrodynamic radius, polydipersion index, zeta potential, morphology, drug content, encapsulation efficiency and stability in accelerated conditions (LUMiSizer). In vitro evaluation of the photodynamic activity of the nanostructured systems was performed through a typical photodegradation experiment of the chemical quencher 1,3-diphenylbenzofuran (DPBF). The release kinetics profile of ClAlPc from the nanocarriers was also studied. The toxicity and biodistribution of nanoparticles were evaluated against the specie Caenorhabditis elegans. The nanostructured systems showed nanometer sizes, low polydispersity indices, negative zeta potential, with high values in modulus, what indicated a good stability, high encapsulation efficiency, nearly 100%. The analyses by LUMiSizer confirmed optimal stability for the MH-b-PMMA@ClAlPc nanoparticles, suggesting a shelf life of at least 3 years. Furthermore, the nanocarriers containing the photosensitizer were able to generate cytotoxic singlet oxygen species when irradiated with laser light (660 nm and power of 30 mW), showing ΦΔ values close to those of free ClAlPc. The nanoparticles showed a controlled and sustained release profile of the drug. In the toxicity study, the nanostructured systems induced a decrease in the larval development of C. elegans, however, at low concentrations, the nanoparticles did not induce nematode lethality. Furthermore, the biosdistribution analyses showed that the nanocarriers were localized mostly in the cells around the intestine, confirming the oral absorption of the nanoparticles. In conclusion, the nanocarriers prepared in this work are promising for carrying hydrophobic photosensitizers for use in PDT.